Circulating Tumour Cells and FOXP3 in Regulatory T-Cells as New Modalities in Cancer Diagnosis and Metastasis Location Prediction - Ikhwan Rinaldi (Interna Publishing, 2023)
Cancer is a complex group of diseases which arises from uncontrolled growth and spread of abnormal cells in the body. The pathophysiology of cancer involves a sequence of events at the cellular and molecular levels, often initiated by genetic mutations or alterations. These mutations can be acquired due to various factors like environmental exposures such as from carcinogens, lifestyle choices, or inherited genetic conditions. When a cell's DNA is damaged or mutated, it can disrupt the normal regulatory mechanisms that control cell division and apoptosis, leading to uncontrolled proliferation and cancer. the intricate interplay between genetic mutations, angiogenesis, hematogenic spread, CTCs, immune cells, and systemic cancer therapy defines the complex landscape of cancer progression and treatment. Understanding the role of immune cells, particularly Tregs marked by FOXP3, as prognostic markers in various cancers, alongside advancements in cancer diagnosis involving CTCs, holds promise in understanding cancer prognosis and improving cancer management. Moreover, ongoing research into alleviating chemotherapy-induced side effects, like HFS offer avenues for improving patient care and treatment outcomes in cancer management.